Exposure to electromagnetic waves for reducing brain health: A bibliometric analysis - Savitri, Ida Ayu Gede Winda; Adnyana, I Made Dwi Mertha; Wahyudi, I Wayan; Dewi, Gusti Ayu Putu Wahyu Purnama; Ariastuti, Indria; Sundari, Ni Luh Putu Ari; Nuartha, Pande Komang Aditya Ryan (PT. Mega Science Indonesia, 2024)
Exposure to electromagnetic waves has been reported to have an adverse impact on human brain health. Various claims have revealed the impact of long-term exposure to electromagnetic waves clinically and nonclinically, but there are no comprehensive studies that explain the effects of electromagnetic wave exposure on human brain health. This study aimed to identify the effects of electromagnetic wave exposure on human brain health. Using a meta-synthesis approach and bibliometric analysis. A total of 271 articles from Scopus, Web of Science and PubMed were screened to obtain 148 terms and analyzed descriptively. The findings from 2004–2024 articles that met the selection criteria resulted in 10 major clusters, 903 networks and 4,020 network strengths. The terms